RESEARCH OF EDUCATIONAL ENVIRONMENT IN PHYSICS STUDY APPLYING PSYCHOLOGIC-PEDAGOGICAL EXAMINATION METHODS - Slipukhina, Irina A.; Menyalov, Sergey М.; Maximov, Sergey L. (Proceedings of National Aviation University (archive), 2008)
The method of examination is one of the most important elements in the algorithm of innovative educational environment creation. It enables to carry out monitoring and get the clearer picture of potential, directions and prospects of the environment development. The article contains some results and conclusions of such research carried out on one of the engineering faculties of National Aviation University.